Prevalence and causes hypersensitivity of teeth in children and young - Gorokhovskiy, V. V.; Shpak, S. V. (Journal of Education, Health and Sport, 2017)
The aim: to study the prevalence and the main etiological factors of hyperesthesia in children and young adults.Materials and methods. We examined 260 people of both sexes, including children aged 13 - 18 y. o. and young adults aged 19 - 25 y. o., dwelling in different regions of Ukraine. All the surveys carried out a survey to establish the etiological factors of increased tooth sensitivity. It was also conducted clinical examination of dental hard tissues by generally accepted method to confirm hyperesthesia symptoms. Those surveyed were divided into 6 groups, depending on gender, age and place of residence or study.Results. Interviewed female patients in groups 1-3 index distribution of hyperesthesia 37.5%,47% and 39%, respectively, in group 4, the index reaches 58,3%, and 5 group is 81.6%,which is high in individuals 6 group index distribution of the hyperesthesia falls sharply to a minimum (29%).Conclusion. Hypersensitivity is a common and recurrent disease in children and young adults The main causes of hyperesthesia in children and young persons (under 25 years) is excessive consumption of juices, waters and sweet food with excessive content of sweet.